JAAR, el lamento de las imágenes - Rodríguez Sickert, Paula (Errante Producciones, 2017)
JAAR the lament of the images observes the creative and personal process of Alfredo Jaar, the contemporary Chilean artist of greater international recognition. For him, art is the last remaining space in society from which it is possible to speak honestly and deeply about social conflicts in a world dominated by consumption and entertainment. A documentary that covers his work exhibited in Finland, Venice, Buenos Aires, Santiago and New York.--